Pengaruh Harga, Promosi dan Produk Terhadap Keputusan Konsumen Membeli Handphone Blackberry di Surabaya - Thyophoida W.S.P. (BIP's JURNAL BISNIS PERSPEKTIF, 2011)
Technological developments that occur when is progressing very rapidly and this is often with the changing times. One of the technological developments that have developed very rapidly is the field of communications technology, especially mobile phones. At this time cell phones have become a necessity for most of the people of Indonesia. Responding to this, the Blackberry mobile phone company offers the benefits inherent in the products it produces, which is where consumers can more easily communicate always obtain the latest information, providing a variety of features, price terjangkauan as well as design and good quality. Problems that would like addressed in this study are: 1. Whether prices, products, and promotions simultaneously affect consumer decisions to buy Blackberry phones in Surabaya? 2. Whether prices, products, and promotions partially affect consumer decisions to buy Blackberry phones in Surabaya? Based on calculations using SPSS for windows 16 known to the adjusted R2 value of 68.5% indicates that purchasing decisions can be explained by variebel free of 68.5% and 31.5% explained by other factors outside the model. that variable pricing, products, and promotions simultaneously influence the purchasing decisions for which the calculated F value 72.660 with a significant 0.000. Based on t test results of tests indicate that: Price variables significantly influence the purchase decision with a value of 5.681 t count bigger than t tables of 2.277 with a significant level of 0.000. Product variables significantly influence the purchase decision with a value of 6.751 for the value t count bigger than t tables of 2.277 with a significant level of 0.000, and promotion variables significantly influence the purchase decision with a value of 2.930 t count bigger than t tables of 2.277 with a significant level of 0.004 Based on the test results are known variables tj most dominant influence on product purchasing decisions which have the greatest value that is equal to 6.751.